Analisis perhitungan biaya produksi menggunakan metode full costing dan variable costing dalam menetapkan harga pokok produksi roti pada Toko Kartini - Maksud, Taufik Rahmat; Manossoh, Hendrik; Maradesa , Djeini (Yayasan Widyantara Nawasena Raharja, 2024)
Production costs are costs that include all costs, either directly or indirectly that can be identified with the activities of processing raw materials into finished products. Cost of goods manufactured is a collection of costs that have been incurred and processed that occur in a process of producing goods consisting of raw material costs, direct labor costs and factory overhead costs. The full costing method is a method for determining the cost of goods manufactured by charging all fixed and variable production costs to the products produced. The variable costing method is a method for determining the cost of goods manufactured by only taking into account variable production costs. The purpose of this study was to determine how to analyze the calculation of production costs using the full costing and variable costing methods in determining the cost of production of bread products at Toko Kartini. This study used qualitative approach with a descriptive analysis. The results of this study show that the calculation of the cost of goods produced when applied the full costing method and variable costing get different results compared to company's method. The full costing method gets bigger results than the company’s method, while the variable costing method gets smaller results than company’s method, as well as the full costing method which gets bigger results than when calculated using the variable costing method.